Birth weight predicts patient outcomes in infants who undergo congenital diaphragmatic hernia repair. (12th December 2022) - Gupta, Vikas S.; Ferguson, Dalya M.; Lally, Pamela A.; Garcia, Elisa I.; Mitchell, Kyle G.; Tsao, Kuojen; Lally, Kevin P.; Harting, Matthew T.
Abstract: Purpose: The purpose of this study was to analyze the clinical characteristics and outcomes of low birthweight (LBW) infants with congenital diaphragmatic hernia (CDH) compared to normal birthweight (NBW) infants with CDH. We hypothesized that LBW was associated with increased mortality, decreased extracorporeal life support (ECLS) utilization, and increased pulmonary morbidity in CDH patients. Methods: Patients in the CDH Study Group from 2007 to 2018 were included. LBW was defined as <2.5 kg. Clinical characteristics and outcomes for LBW patients were compared to normal birthweight (NBW) patients using univariate and multivariable analyses. Results: Of 5, 586 patients, 1, 157 (21%) were LBW. LBW infants had more congenital anomalies and larger diaphragmatic defects than NBW infants. ECLS utilization was decreased, and overall mortality was increased among LBW infants compared to NBW infants. A 1 kg increase in birthweight was associated with 34% higher odds of survival after repair (adjusted Odds Ratio 1.34, 95% CI 1.03–1.76; p  = .03). LBW infants had longer durations of mechanical ventilation and were more likely to require supplemental oxygen at 30 days and at the time of discharge. Conclusion: LBW is a risk factor for mortality and pulmonary morbidity in CDH. Prolonged oxygen requirement and increased length of stay are important considerations when managing this population.